2017
DOI: 10.1136/neurintsurg-2017-013156
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for and outcomes of intraprocedural rupture during endovascular treatment of unruptured intracranial aneurysms

Abstract: Aneurysms in the AcomA and with a small dome size are likely to be risk factors for IPR. IPR induced by microcatheters can result in poor outcomes. The rate of IPR-associated thromboembolic complications is high, and IPR itself is associated with acute hydrocephalus. If managed appropriately, however, most patients with IPR can survive without neurological deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
0
21
2
Order By: Relevance
“…And they also reported the rates of good clinical outcomes of IARs induced by coils, micro-guidewires, and microcatheters were 90%, 100%, and 57%, respectively. 7 Over-packing of the aneurysm, oversized coils, and the use of stiff 3D coils have been reported to be associated with IARs. 8 The higher risk of rupture in small aneurysms is believed to be due to the increased restriction of microcatheter movement within the aneurysm, resulting in greater stress within the aneurysm sac.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…And they also reported the rates of good clinical outcomes of IARs induced by coils, micro-guidewires, and microcatheters were 90%, 100%, and 57%, respectively. 7 Over-packing of the aneurysm, oversized coils, and the use of stiff 3D coils have been reported to be associated with IARs. 8 The higher risk of rupture in small aneurysms is believed to be due to the increased restriction of microcatheter movement within the aneurysm, resulting in greater stress within the aneurysm sac.…”
Section: Mechanismmentioning
confidence: 99%
“…And they also reported the rates of good clinical outcomes of IARs induced by coils, micro-guidewires, and microcatheters were 90%, 100%, and 57%, respectively. 7…”
Section: Iar During Coilingmentioning
confidence: 99%
“…In addition, intraoperative rupture has been reported to more likely occur in small aneurysms than in large aneurysms. 15) Improving the visibility of the cistern around the aneurysm using SMART may improve the detectability of intraoperative rupture.…”
Section: Discussionmentioning
confidence: 99%
“…During endovascular embolization of intracranial aneurysm, the transmural pressure gradient of the aneurysm sac must remain constant 2 , 9 , 10 to decrease the risk of rupture, estimated to be 1.4% of the cases. 11 Furthermore, preventing the ischemia and bleeding that can occur at different moments, during or shortly after the procedure, requires a strict and continuous control of the hemodynamic and respiratory parameters, in particular during the induction of anesthesia and the awakening period. As studies in other settings have demonstrated the benefit of using SGD to reduce the deleterious hemodynamic impact of airway manipulation during induction and emergence of anesthesia in comparison to OTI, it could be speculated that they may contribute to reduce the risk of aneurysm rupture and postoperative intracranial bleeding.…”
Section: Discussionmentioning
confidence: 99%